Desempenho de sementes de trigo recobertas com silicato de alumínio - Fonseca, Daniel Ândrei Robe (2013)
The present study, we used seeds of wheat, cv Fundacep horizon coated with six doses of aluminum silicate (0, 20, 30, 40, 50 and 60g per 100 kg seed). We conducted two research studies in order to verify the influence of the silicon used by seed, and to evaluate the physiological performance and yield components. In the first paper we studied the behavior of the physiological quality of seeds coated with aluminum silicate. The second was carried out the experiment evaluating the absorption by the plants and silicon influence on the rate of chlorophyll and the components of yield and quality physiological seed. The results showed that aluminum silicate improves the physiological quality of seeds have been subjected to stress and yield of wheat plants grown from seeds coated with aluminum silicate.